RANCANG BANGUN SISTEM PEMBERIAN PAKAN DAN PENGATURAN pH AIR SECARA OTOMATIS PADABUDI DAYA IKAN LELE BERBASIS ATMEGA 16 MENGGUNAKAN MEDIA SMARTPHONE - Mey Hajarini Siregar; Mulkan Iskandar Nasution (UIN Sumatera Utara Medan, 2021)
Research has been carried out that aims (i) to design a feeding system and water pH regulation in catfish farming automatically, (ii) to assemble and build a control circuit with existing electronic components and sensors, (iii) to apply the IoT system to pH controller made to be controlled remotely. The tool is designed to control the pH of the water by means of circulation and for measuring the pH of the water in the catfish pond, it is carried out periodically using a pH sensor of type PH4502C. The system uses the RTC DS1307 digital clock module to determine the feeding schedule. Smartphone communication with control circuits uses internet media for data transfer and commands. Regulates feeding in catfish ponds and integrates with smartphones. The design of the feeding system and pH regulation in catfish farming automatically, the tool can provide feed and regulate the pH of the water automatically according to a schedule that has been set with the program that has been made. The circuit is assembled and built into the chassis by installing all electronic components and sensors on the PCB. Such as the process of automation of feeding using a servo motor, to measure the pH of the water using a pH sensor and setting the pH of the water using a water pump. By using the RTC as a digital clock to provide time information on the microcontroller so that the program can run according to what has been made. The application of the IoT system to the pH controller and feeding device that is made is controlled remotely. This tool is able to send information and commands from two directions using an adapter device from Wifi, namely the MCU Node. The MCU node is set to be related to the Wifi hotspot and connectivity with the Blynk server on the smartphone. Menu settings are made according to the required display, namely the pH display, buttons to activate and deactivate the water pump, feeding, and notifications if there is a change in the pH of the water or if the pH of the water is unstable